Female Students' Interpretation and Attitudes toward the Representation of Islamic Values, Islamic Boarding Schools, and Gender Relations in the Film Perempuan Berkalung Sorban - Siswati, Endah; Zami, Qomaruzzaman Azam; Susanti, Laili Neni (Universitas Tanjungpura, 2025)
Films often serve as a medium of social representation that shapes how audiences understand religious values, culture, and gender relations. This study aims to analyze how female university students, as the audience, respond to the representation of Islamic values, pesantren life, and gender relations in the film Perempuan Berkalung Sorban, as well as to explore the internal meaning-making processes formed and the responses that emerge after watching the film. The research uses a descriptive qualitative approach with the Stimulus–Organism–Response (SOR) theoretical framework. The film is positioned as the stimulus presenting religious and gender-based representations; the cognitive–affective processes of the female students serve as the organism; and their emotional reactions, attitudes, and behavioral intentions constitute the response. Data were collected through observation, in-depth interviews with seven Muslim female students, and film document analysis. The findings show that the students interpret the film as a critique of the misuse of patriarchal religious interpretations and as a reflection of certain social realities related to gender inequality in pesantren settings and in society. The meaning-making process occurs through comparing normative Islamic values they believe in with the patriarchal social practices portrayed in the film. Audience responses include emotional reactions (anger, sadness, discomfort), changes in attitudes toward gender issues and religious interpretation, and emerging intentions to engage in discussions, express opinions, and promote gender equality in their social environment. This study affirms that film can function as an effective stimulus in shaping audiences’ critical awareness regarding Islamic values, pesantren life, and gender relations.